Acute Health Consequences from Electronic Cigarettes: A Narrative Review: Acute Health Consequences from E-cigarettes - Laohaprapanon, Sawanya; Saengow, Udomsak (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Electronic cigarettes (e-cigarettes) is relatively recently introduced to the market. Its long-term effects are still unclear and require years of research. On the other hand, knowledge about the short-term effects of e-cigarettes is emerging. The purpose of this review was to examine the current literature on the acute health consequences associated with the e-cigarette. We used pre-specified keywords to conduct searches in academic databases of articles published between 2011 and 2020. This review focused on acute health consequences of e-cigarettes in humans that can be directly attributed to the e-cigarette. Burns and injuries associated with device explosion, e-liquid intoxication, e-cigarette or vaping product use-associated lung injury, and pneumomediastinum were identified as acute health consequences associated with e-cigarettes. Except for pneumomediastinum, these acute health consequences are unique to an e-cigarette that are unlikely to be caused by a conventional cigarette. In the short term, the e-cigarette is likely more harmful than the conventional cigarette. Tightening safety regulations on the manufacturing, distribution, and sale of e-cigarette devices is recommended. Compulsory child-resistant containers for e-liquid containers, banning or restriction the use of colorful labels on e-liquid containers, and compulsory warning labels on e-liquid containers are recommended to prevent child’s ingestion of e-liquid.